Inflammasome-Associated Nucleotide-Binding Domain, Leucine-Rich Repeat Proteins and Inflammatory Diseases() - Jha, Sushmita (2009)
The nucleotide-binding domain, leucine-rich repeat (NLR) proteins are a recently discovered family of intracellular pathogen and danger signal sensors. NLRs have emerged as important contributors to innate immunity in animals. The physiological impact of these genes is increasingly evident, underscored by the genetic association of variant family members with an array of inflammatory diseases. The association of mutations in NLR genes with autoinflammatory diseases indicates an important function of these genes in inflammation in vivo. This review summarizes the role of the inflammasome NLR proteins in innate immunity and inflammatory diseases and explores the possible utility of some of these NLRs as pharmacological targets.